2022
DOI: 10.1021/acsnano.2c01547
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Passivation Engineering for Highly Efficient Perovskite Solar Cells with a Fill Factor over 83%

Abstract: Charge carrier nonradiative recombination (NRR) caused by interface defects and nonoptimal energy level alignment is the primary factor restricting the performance improvement of perovskite solar cells (PSCs). Interfacial modification is a vital strategy to restrain NRR and enable high-performance PSCs. We report here two interfacial materials, PhI-TPA and BTZI-TPA, consisting of phthalimide and a 2,1,3-benzothiadiazole-5,6-dicarboxylicimide core, respectively. The difunctionalized BTZI-TPA with imide and thia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
46
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 66 publications
1
46
0
Order By: Relevance
“…The PL intensity of perovskite film deposited on the AMD treated PTAA HTL is the lowest, which may be attributed to the best charge transport ability of AMD modified PTAA HTL and the fastest charge transfer due to the formation of p–n homojunction at the HTL/perovskite buried interface. [ 36 ] Similarly, the perovskite film deposited on the AMD treated Poly‐TPD HTL exhibits lower PL intensity compared with those deposited on the pristine and CMD treated Poly‐TPD HTLs. Figure 6b shows the TRPL spectra of perovskite films deposited on different PTAA and Poly‐TPD HTLs, which can be fitted with a bi‐exponential decay model (y=A1exp(xτ1)+A2exp(xτ2)+y0$y = {A_1}\exp \left( { - \frac{x}{{{\tau _1}}}} \right) + {A_2}\exp \left( { - \frac{x}{{{\tau _2}}}} \right) + {y_0}$) and the fitting parameters are shown in Table S8, Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…The PL intensity of perovskite film deposited on the AMD treated PTAA HTL is the lowest, which may be attributed to the best charge transport ability of AMD modified PTAA HTL and the fastest charge transfer due to the formation of p–n homojunction at the HTL/perovskite buried interface. [ 36 ] Similarly, the perovskite film deposited on the AMD treated Poly‐TPD HTL exhibits lower PL intensity compared with those deposited on the pristine and CMD treated Poly‐TPD HTLs. Figure 6b shows the TRPL spectra of perovskite films deposited on different PTAA and Poly‐TPD HTLs, which can be fitted with a bi‐exponential decay model (y=A1exp(xτ1)+A2exp(xτ2)+y0$y = {A_1}\exp \left( { - \frac{x}{{{\tau _1}}}} \right) + {A_2}\exp \left( { - \frac{x}{{{\tau _2}}}} \right) + {y_0}$) and the fitting parameters are shown in Table S8, Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…It is found that the grain size and crystallinity of the perovskite film are increased when it is deposited on SnO 2 @B 12 in comparison to that on the pristine SnO 2 (Figure 2). The larger grain size and better crystallinity can effectively suppress the moisture permeation at grain boundaries, resulting in improved environmental stability for the PSCs based on the SnO 2 @B 12 ETLs [3c,d] …”
Section: Resultsmentioning
confidence: 99%
“…Additionally, SnO 2 is an excellent ETL candidate due to its strong electron mobility, suitably energy levels, and intrinsic superior stability of the inorganic nature, which has been extensively studied in photoelectricity fields, [8] especially for renewable energy technologies [3d,5,8f] . Many strategies have been explored on enhancing the quality of SnO 2 and perovskites to boost photovoltaic performance.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Perovskite solar cells (PSCs) have made tremendous progress in power conversion efficiency (PCE), which increased from 3.8% in 2009 to 24.8% in 2020. [2][3][4][5][6] PSCs reveal numerous advantages for effective solar energy conversion due to their outstanding semiconductor properties, [7] such as significant optical absorption in the wavelength ranges of 400-800 nm, [8] low defect density, [9] high mobility, [10] long carrier lifetime and diffusion length, [11] as well as solution processability with low cost. [12] Although the PCE of PSCs reached 25.7%, [13] there is still space to further improve the PCE of the PSCs or a system through the efficient utilization of the whole solar spectrum.…”
Section: Introductionmentioning
confidence: 99%